HARMONISASI SAINS DAN AGAMA: PENGEMBANGAN MODUL BIOLOGI BERBASIS INTERKONEKSI SAINS DAN NILAI-NILAI AGAMA - Idham Kholid; Supriyadi Supriyadi (Bioedukasi: Jurnal Pendidikan Biologi FKIP UM Metro, 2021)
Study on integration and interconnection of science and religion in education has been developed for quite a long time. However, most science teachers, especially biology teachers, do not understand enough how to integrate science and religion in biology learning. This research aims to develop a biology learning module based on the interconnection of science and religion in the model of guided inquiry learning. Developing this model is urgent to develop meta-cognitive knowledge and skill of prospective teachers in biology learning based on the interconnection of science and religion. This research uses the research and development methods (R&D) with 4D steps: Define, Design, Develop, Disseminate. Data is gathered from expert validation, small group experiment, and the response of the experimental subject. The result shows that this module is very good at the following aspects: construction (score 94,5%), didactic (score 94%), technic (score 95%), religion (score 92%), and language (score 87%). In addition, students (N=35) stated that this module is very interesting (score 95%). They also aid that this module is easily used (score 90,22%, efficient (score 92,85%), and very clear (score 88,14). In conclusion, this developed learning module based on the interconnection of science and religion is adequate to implement for biology learning. This module also contributes to education institutions by presenting alternative references on the inter-discipline approach. Kata kunci::   harmonisasi sains dan agama, pengembangan, modul biologi